UPAYA KEPALA MADRASAH DALAM MENINGKATKAN MANAJEMEN SARANA DAN PRASARANA PENDIDIKAN DI MTS AR-RIDHO SENTUL - Abdul Hafied Syaripuddin; Omon Abdurakhman; Irman Suherman; Syukri Indra (Fakultas Agama Islam dan Pendidikan Guru, 2022)
Principal of Madrasah as manager must have a strategy to develop educational facilities and infrastructure. Because, as one of the indicators that is most easily measured to determine school qualifications, it can be seen from the complete facilities and infrastructure to support the learning process in schools. The purpose of this research is to get an explanation of the main strategies in developing facilities and infrastructure, and the impact or influence on the quality of learning, which is another benefit of this research is expected to make a positive contribution to students of Educational Management, who will devote themselves in the world of education both educator and Head of Madrasa. This study uses a qualitative approach with descriptive methods; data collected through interviews, observation and documentation studies. After the required data is collected, the authors present the data obtained in accordance with the facts in the field. Based on the results of the study, it shows that the efforts of madrasah principals in improving the management of facilities and infrastructure based on the above research include: establishing cooperation with school committees or other agencies, carrying out teacher training in the internal environment at school, giving workshops to staff or teachers on managerial facilities and infrastructure at in schools or in other institutions, increasing school community awareness about the importance of the existence of facilities and infrastructure through guidance, counseling, and other activities, procuring facilities and infrastructure in accordance with school needs and making improvements and maintenance of school facilities and infrastructure.